The theory of reasoned action and patient compliance during orthodontic treatment - Bos A, Hoogstraten J, Prahl-Andersen B. (Blackwell Synergy, 2005)
The aim of the present study was to investigate the potential of the theory of reasoned action (TRA) for the prediction and understanding of patients’ intention to comply during orthodontic treatment and to analyze the effect of two additional variables in the model, namely perceived behavioral control and anticipated regret.